Multicomponent intervention versus usual care for management of hypertension in rural Bangladesh, Pakistan and Sri Lanka: study protocol for a cluster randomized controlled trial - Tazeen H. Jafar; Imtiaz Jehan; H. Asita de Silva; Aliya Naheed; Mihir Gandhi; Pryseley Assam; Eric A. Finkelstein; Helena Legido Quigley; Marcel Bilger; Aamir Hameed Khan; John David Clemens; Shah Ebrahim; et al. (Trials, 2017)
Abstract Background High blood pressure (BP) is the leading attributable risk for cardiovascular disease (CVD). In rural South Asia, hypertension continues to be a significant public health issue with sub-optimal BP control rates. The goal of the trial is to compare a multicomponent intervention (MCI) to usual care to evaluate the effectiveness and cost-effectiveness of the MCI for lowering BP among adults with hypertension in rural communities in Bangladesh, Pakistan and Sri Lanka. Methods/design This study is a stratified, cluster randomized controlled trial with a qualitative component for evaluation of processes and stakeholder feedback. The MCI has five components: (1) home health education by government community health workers (CHWs), (2) BP monitoring and stepped-up referral to a trained general practitioner using a checklist, (3) training public and private providers in management of hypertension and using a checklist, (4) designating hypertension triage counter and hypertension care coordinators in government clinics and (5) a financing model to compensate for additional health services and provide subsidies to low income individuals with poorly controlled hypertension. Usual care will comprise existing services in the community without any additional training. The trial will be conducted on 2550 individuals aged ≥40 years with hypertension (with systolic BP ≥140 mm Hg or diastolic BP ≥90 mm Hg, based on the mean of the last two of three measurements from two separate days, or on antihypertensive therapy) in 30 rural communities in Bangladesh, Pakistan and Sri Lanka. The primary outcome is change in systolic BP from baseline to follow-up at 24 months post-randomization. The incremental cost of MCI per CVD disability-adjusted life years averted will be computed. Stakeholders including policy makers, provincial- and district-level coordinators of relevant programmes, physicians, CHWs, key community leaders, hypertensive individuals and family members in the identified clusters will be interviewed. Discussion The study will provide evidence of the effectiveness and cost-effectiveness of MCI strategies for BP control compared to usual care in the rural public health infrastructure in South Asian countries. If shown to be successful, MCI may be a long-term sustainable strategy for tackling the rising rates of CVD in low resourced countries. Trial registration ClinicalTrials.gov, NCT02657746. Registered on 14 January 2016.